Characteristics of Childhood Steroid-Induced Glaucoma patients in National Eye Center, Cicendo Eye Hospital, Bandung, Indonesia from 2007 to 2011 - Badriyah, Indri Nurul; Irfani, Irawati; Rakhmilla, Lulu Eva (Althea Medical Journal, 2015)
Background: The prevalence of childrenâs blindness in developing countries is still high especially in Asian countries. This childrenâs blindness influences their motoric, social and emotional developments and their chances to get education. One of the causes is steroid-induced glaucoma. The aim of the study was to identify the characteristics of childhood steroid-induced glaucoma in National Eye Center, Cicendo Eye Hospital, Bandung, Indonesia.Methods: A descriptive study was conducted to 22 medical records of childhood steroid-induced glaucoma patients in National Eye Center, Cicendo Eye Hospital Bandung from 2007â2011. The inclusion criterias were medical records contained complete demographic (age, sex, address and socioeconomic status), clinical (visual acuity, intraocular pressure, cup-disc ratio, underlying eye disease, working diagnosis, treatment and patientâs compliance to follow up) and risk factor (type and route of administration of steroid and duration of steroid usage).Results: Majority of patients were boys (73%), aged 4â7 years old (41%), from Bandung (55%), with moderate socioeconomic condition (73%). Most of the patients experienced blindness (64%), intraocular pressure around 20â30 mmHg (33%), cup-disc ratio above 0.4 (77%). The underlying eye disease was conjunctivitis vernalis (95%). They were treated by medicamentosa or trabeculectomy. The most common used steroid contained dexamethasone (100%) for more than 1 year of usage (64%). Patientsâs compliance to follow up was mostly good (59%).Conclusions: Most of the patients with steroid-induced glaucoma is still very young and the use of topical dexamethasone to treat conjunctivitis vernalis for a long time leads to steroid-induced glaucoma.Â DOI:Â 10.15850/amj.v2n3.558